Soviet Propaganda Posters of the Stalinist Era - Ciesielka, Joanna (Populismo y propaganda: entre el presente y el pasado, 2020)
The visual culture represents relevant live evidence of a nation and of a country in the determined period of its development. The aim of my article is to analyse several Soviet propaganda posters of the Stalinist era created in the years 1924–1953 which provide an interesting image of the Soviet Union of the time. The analysed posters concern the issues such as war, enemies of communism, life of the nation and obviously, Stalin, a leader and dictator who was believed to hold URSS towards happiness and welfare. The subject of the analysis shall be both visual content of the posters and linguistic message conveyed by them.